Genomic and chromosomal damage in the marine mussel Mytilus galloprovincialis: Effects of the combined exposure to titanium dioxide nanoparticles and cadmium chloride. (October 2015) - Rocco, L.; Santonastaso, M.; Nigro, M.; Mottola, F.; Costagliola, D.; Bernardeschi, M.; Guidi, P.; Lucchesi, P.; Scarcelli, V.; Corsi, I.; Stingo, V.; Frenzilli, G.
Abstract: Titanium dioxide nanoparticles (TiO2 -NPs) continuously released into waters, may cause harmful effects to marine organisms and their potential interaction with conventional toxic contaminants represents a growing concern for biota. We investigated the genotoxic potential of nanosized titanium dioxide (n-TiO2 ) (100 μg L −1 ) alone and in combination with CdCl2 (100 μg L −1 ) in Mytilus galloprovincialis after 4 days of in vivo exposure. RAPD-PCR technique and Micronucleus test were used to study genotoxicity. The results showed genome template stability (GTS) being markedly reduced after single exposure to n-TiO2 and CdCl2 . Otherwise, co-exposure resulted in a milder reduction of GTS. Exposure to n-TiO2 was responsible for a significant increase of micronucleated cell frequency in gill tissue, while no chromosomal damage was observed after CdCl2 exposure as well as after combined exposure to both substances. Highlights: TiO2 -NPs can interact with marine contaminants modifying their toxicity. Single exposure to n-TiO2 and CdCl2 reduces in vivo DNA stability in mussels. n-TiO2 increases in vivo micronucleated cell frequency in Mytilus galloprovincialis . No synergic effect is observed after co-exposure to n-TiO2 /CdCl2 .